Career anxiety and covid-19 phobia in students of the faculty of nursing of Universitas Padjadjaran - Ofni Stephany Lumban Raja; Ati Surya Mediawati; Theresia Eriyani; Maria Komariah; Iwan Shalahuddin (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Covid-19 is a global pandemic that is still happening today, the spread of the virus affects aspects of education that are closely related to students. Nursing students are one of the individuals affected by Covid-19, especially professional students who are undergoing clinical practice education. Professional students can experience problems such as career anxiety and  phobia of Covid-19 which can trigger career anxiety. This study aimed to discover the description of career anxiety and Covid-19 Phobia among professional students of class 41 and 42 of the Faculty of Nursing, Universitas Padjadjaran during the Covid-19 pandemic era. The design of this study is quantitative descriptive using hypothetical statistical data analysis and sampling technique using the total sampling (n=176). The instruments used in this study were Career Anxiety Scale (CAS) and Covid-19 Phobia Scale (C19P-S). The results showed that the description of career anxiety and Covid-19 Phobia among professional students of class 41 and 42 of the Faculty of Nursing, Universitas Padjadjaran during the Covid-19 pandemic era was in the moderate category (49.4%) and (55.1%). The conclusion in this study is professional students of class 41 and 42, experience career anxiety and Covid-19 Phobia in the moderate category. Therefore the results of this study may be used as advice for educational institutions to pay attention to students who experience career anxiety and Covid-19 Phobia and support students to reduce anxiety disorders by designing special programs such as counseling and career guidance.